Analisis Penyertaan Modal PT. PDAM di Kota X - Pandji Anoraga (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2020)
The purpose of this study is to determine the feasibility of regional capital participation both economically and legally. The second is as a basis for formulating policies on the implementation of PDAM X Equity Participation.The methodology used in PDAM X's equity analysis is SWOT analysis, portfolio management, risk management and feasibility studies (organizational & human resources aspects, market and marketing aspects, production and operation aspects, audited data-based financial aspects). Financial aspects as a result of improved service and production are increased sales, cost efficiency and profit levels. From a financial aspect, the PDAM service portfolio must answer the problem, however it is very dependent on the funding for operating activities, and on the other hand, it must be able to meet the growing profitability. If there is additional investment funds, the direction is to be able to increase production capacity, service and ultimately be able to increase the volume of water services and be able to increase the profitability of PDAMs. Thus it can be concluded that the project can improve service to consumers and from better service, better water sales will be obtained and better profits